Telaah Epistemologis Pendekatan Saintifik Mata Pelajaran Pendidikan Agama Islam - Kusaeri, Kusaeri (Program Pascasarjana UIN Sunan Ampel Surabaya, 2015)
This article seeks to find out the intersection between scientific approach and Islamic religious education as a subject matter. The scientific approach adopts scientific steps in building scientific knowledge, i.e. such featuring dimensions as observation, reasoning, inquiry, validation anD and description of scientific truth. Since the scientific approach is regarded as too empirical, rational and logical. In Cartesian sense, it contradicts the logical structure of the subject of Islamic religious education. Five aspects of Islamic religious education (the QurâÃ¢n, HadÃ®th, AqÃ®dah Akhlaq, Fiqh, history of Islamic culture, and Arabic language) have different characteristics, even demand a non-scientific logics such as intuition and revelation. AqÃ®dah (belief), for example, which consists of the doctrine of monotheism (tawhid) is difficult to be scrutinized through empirical evidence. There are some other examples in this field which are difficult to be analyzed by means of scientific approach. Through library research, this article nevertheless finds that the logic of scientific approach and Islamic religious education can be integrated, since revelation and reason are mutually supportive.